Alizarin increase glucose uptake through PI3K/Akt signaling and improve alloxan-induced diabetic mice. (17th January 2019) - Xu, Lanting; Xing, Meimei; Xu, Xiaoqing; Saadeldeen, Fatma SA; Liu, Zhenhua; Wei, Jinfeng; Kang, Wenyi
Aim: Alizarin (AZ), that can be isolated from Rubia cordifolia, has biological activities such as antioxidation and anti-inflammatory. This study aimed to investigate the effect of AZ on glucose and lipid metabolism disorders in alloxan-induced diabetic mice and also explored the effect of AZ on insulin resistance in 3T3-L1 adipocytes.Results: The research showed that AZ could decrease fasting and postprandial blood glucose, TG, TC and MDA, and it could also increase liver glycogen levels and SOD activity in diabetic mice. AZ could significantly improve the glucose uptake of 3T3-L1 adipocytes under insulin resistance, and could also increase GLUT4 protein expression levels, IRS-1 and Akt protein phosphorylation.Conclusion: These results showed that AZ has the potential to reduce blood sugar and improve insulin resistance.